ANALISIS PENERIMAAN SISTEM INFORMASI E-PUSKESMAS DI KABUPATEN BADUNG BERDASARKAN TECHNOLOGY ACCEPTANCE MODEL - Alvian, Viky Yudi; Widarsa, I Ketut Tangking (ARCHIVE OF COMMUNITY HEALTH; Vol 6 No 2 (2019): Desember 2019, 2019)
ABSTRACT There were some problems on e-Puskesmas's implementation in Badung Regency. The first problem is the quality of internet connection is not good in some areas. This problem makes the operator feels difficult when input the patient’s data because this system needs good internet connection. The second problem is an error on patient’s online referral feature. This research was conducted to know the acceptance level of the system. This research was an analytic study with cross sectional design. The sample size was 65 staff that operate e-Puskesmas. The sampling methods was cluster random sampling. The research instruments was a questionnaire that based on Technology Acceptance Model. The results showed that 76,92% of respondent stated e-Puskesmas is useful, 61,54% of respondent stated e-Puskesmas is easy to use, and 80% of respondent accepted the usage of e-Puskesmas. However, still there some problem such as increase the operator’s workload, mismatched data on the system compared with manual record, bad internet connection, the user interface is not friendly by some user, lack of ICD-X code, errors on patients referral feature, and still no feature to make a drug request to pharmacy storage. This system’s implementation still need an improvement such as the improvement of the internet connection quality, and adding more staff to decrease operator’s workload, system enhancement to minimize system error, conduct staff training before system update, adding the ICD-X code feature to the system, improvement of the patients referral feature, and adding the drug request feature to the pharmacy storage. Keywords: The operator's acceptance level, e-Puskesmas Information System, Technology Acceptance Model (TAM)